Efektivitas Toko Milik Rakyat (TOMIRA) dalam Mewujudkan Pemberdayaan Masyarakat di Kabupaten Kulon Progo Tahun 2018 - Rosi Indri Isyaroh; Muhammad Eko Atmojo (Social and Political Sciences Faculty, Widya Gama Mahakam Samarinda University, 2020)
The rise of modern shops or network shops has caused problems in the Kulon Progo community. To solve the existing problems, the Regional Government of Kulon Progo issued a policy in the form of a Regional Regulation. Regional Regulation Number 11 of 2011 concerning Protection and Empowerment of Traditional Markets and the Arrangement of Modern Shopping Centers and Stores. The special thing about this regulation is that there is a zoning system where the distance between modern shops or networking with traditional markets must be 1000 meters. Discrepancy in regulations that have been made with the reality gets a response from the Kulon Progo Regional Government by giving options such as not extending permits, being closed or taking over to the manager of the minimarket. Take Over here is defined as land acquisition so that the government does not bother to start or reopen the store under the name TOMIRA (Toko Milik Rakyat). The Kulon Progo Regent often intensified the